2014
DOI: 10.1016/j.jalz.2014.05.1751
|View full text |Cite
|
Sign up to set email alerts
|

R47H TREM2 variant increases risk of typical early‐onset Alzheimer's disease but not of prion or frontotemporal dementia

Abstract: We find p.R47H is a risk factor for AD, but not frontotemporal dementia or prion disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 31 publications
4
95
0
Order By: Relevance
“…Along with the failure to find any association between specific TREM2 allelotypes and sporadic CJD (Slattery, et al, 2014), the findings described here add to the evidence that TREM2 is not a major determinant of prion pathogenesis. This fact is unexpected and sets prions apart from other neurodegenerative diseases such AD, FTD, PD, and ALS.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Along with the failure to find any association between specific TREM2 allelotypes and sporadic CJD (Slattery, et al, 2014), the findings described here add to the evidence that TREM2 is not a major determinant of prion pathogenesis. This fact is unexpected and sets prions apart from other neurodegenerative diseases such AD, FTD, PD, and ALS.…”
Section: Discussionsupporting
confidence: 47%
“…These findings have spurred numerous studies addressing the association between TREM2 and AD and other neurodegenerative diseases. Although negatives have been reported (Jiao, et al, 2014,Miyashita, et al, 2014,Ruiz, et al, 2014,Yu, et al, 2014, the association between TREM2 variants and AD has been confirmed by most studies (Benitez, et al, 2013,Giraldo, et al, 2013,Gonzalez Murcia, et al, 2013,Luis, et al, 2014,Slattery, et al, 2014. Moreover, TREM2 variants were also found to be associated with frontotemporal dementia-like syndrome or FTD (Borroni, et al, 2014,R.…”
Section: Introductionmentioning
confidence: 91%
“…We also included known early‐onset AD genes and genes implicated in earlier sequencing efforts in LOAD 1, 2, 3, 4, 5, 6, 8, 9, 10, 11, 12, 13, 14, 15, 16. Candidate genes evaluated included: APP, PSEN1, PSEN2, GRN, MAPT, TREM2, PLD3, APOE, ABCA7, SORL1, CR1, BIN1, CD2AP, EPHA1, CLU, MS4A6A, PICALM, CD33, HLA‐DRB5, HLA‐DRB1, PTK2B, SLC24A4, RIN3, INPP5D, MEF2C, NME8, ZCWPW1, CELF1, FERMT2, CASS4, TREML2, and AKAP9 .…”
Section: Methodsmentioning
confidence: 99%
“…Common variants identified through GWAS may not have functional consequences, simply reflecting linkage disequilibrium with the unobserved causal variants. It is also possible that these causal variants are rare and have large effects, such as TREM2, 7, 8, 9, 10, 11, 12, 13 and are not covered by commercially available GWAS platforms. In fact, putatively damaging variants have already been identified (for example TREM2 , SORL1, and ABCA7 ) in some of these LOAD susceptibility loci, advancing our understanding of disease risk 14, 15, 16…”
Section: Introductionmentioning
confidence: 99%
“…Finally, 14 studies were included in the meta-analysis. 13 studies for rs75932628 [11,12,18,19,21,[27][28][29][30][31][32][33][34], 3 studies for rs104894002 [11,32,35], and 4 studies for rs143332484 [12,28,31,32,35]. The selected study characteristics and allele information are shown in Tables 1 and 2, respectively.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%